Implementation of Radius Server–Based User Management on the WLAN Network of Dinas PUBMTR South Sumatra Province Using RADIUSdesk - Rizky Widiansyah (Institute of Information Technology and Social Science (IITSS), 2025)
Wireless Local Area Network (WLAN) technology is widely utilized across government offices, private companies, schools, and healthcare institutions. The Dinas Pekerjaan Umum, Bina Marga, dan Tata Ruang (PUBMTR; Office of Public Works, Highways, and Spatial Planning) of South Sumatra Province is one of the government institutions relying on WLAN technology to support operational activities and internet-based services. However, the agency frequently encounters challenges in managing and authenticating WLAN users, resulting in the absence of differentiation between employee and non-employee access. This condition causes network instability, bandwidth degradation, and operational disruptions during peak usage. This study proposes the implementation of a Radius Server–based user-management system to provide differentiated authentication for employees and ensure more secure, stable WLAN operations. The research methodology includes problem analysis, system design, Radius Server implementation using RADIUSdesk, and WLAN testing. The results indicate that the deployment of Radius Server–based user management using RADIUSdesk successfully improves WLAN management efficiency, simplifies user administration, and enhances network security.